The Israelite covenant in ancient Near Eastern context - Miller, Robert D. 1966-2023 (2008)
Much study of the Israelite covenant has focused on their similarities with ancient Near Eastern treaties. This study proposes that the biblical covenant instead bears greater resemblance to texts composed by vassals of the Neo-Assyrian empire. The best example of such texts is the Barrakab inscription from ancient Samal. It is suggested that Neo-Assyrian propaganda was used in the Barrakab inscription and was likewise adopted by ancient Israelites and altered to describe the relation of Yahweh to his people.
Viele Studien zum israelitischen Bund beschäftigen sich mit dessen Ähnlichkeiten mit den alten Bündnissen des Nahen Ostens. Diese vorliegende Arbeit schlägt vor, dass der biblische Bund größere Ähnlichkeit mit den Texten hat, die von den Untertanen des Neo-Assyrische Reichs verfasst wurden. Das beste Beispiel solcher Texte ist die Barrakab-Inschrift aus dem alten Samal. Man kann annehmen, dass die Neo- Assyrische Propaganda in der Barrakab-Inschrift verwendet wurde und gleichfalls von den alten Isrealiten angenommen und verändert wurde, um die Beziehung Jahwes zu seinem Volk zu illustrieren.
Reproduktion
Keywords: Bund Gottes; Alter Orient